Learning Media Development Android Based on Basic Programming Subjects in a Pandemic Period - Nailul Huda; Marsono Marsono; Yoto Yoto (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This research and development aims to develop products in the form of android-based learning media in Basic Programming subjects. The development carried out follows the stages of the ADDIE development model. The level of media feasibility is seen from the results of product validation. The results of material expert validation show the percentage of 90% which consists of content, presentation and contextual aspects. In addition, the results of media expert validation showed a percentage of 87.50% which consisted of aspects of appearance, content and writing. The results of the attractiveness test of the small group trial showed the percentage reached 95.71%. It can be concluded that android-based learning media in Basic Programming subjects is very feasible to use in learning.